Attitudes and knowledge of medical students concerning prevention and pharmacotherapy of COVID-19 infection in Serbia - Ivanišević, Milica (Medicinski podmladak, 2024)
Introduction: COVID-19 infection represents a worldwide health issue. In order to prevent the infection, it is necessary to possess adequate knowledge regarding virus itself, transmission routes, clinical forms of disease and prevention measures. Also, it is crucial to stay informed about protocols and pharmacotherapeutic options in the treatment of patients infected with SARS-CoV-2 virus. Aim: The aim of this study was to investigate knowledge and attitudes about prevention and pharmacotherapy of COVID-19 infection among students of Faculty of Medicine, University of Belgrade as well as compare differences between 1st, 3rd and 6th year students.Material and methods: Cross-sectional study was conducted among 479 students of all six years of study. Questionnaire was distributed online and it was available between 30th November and 20th December 2021. Results were obtained and analyzed in statistical software SPSS 22.0 (IBM Corp. IBM SPSS Statistics for Windows. Armonk, NY: IBM Cor; 2017).Results: Most of the students that took the part in survey were females (72%) and majority of our participants were vaccinated against COVID-19 infection at the time of the survey (92.7%). Vaccination rate in 1st year students was 78.8%, in 3rd year 97.3% and 97.4% in 6th year students. Different than the 6th year students, 1st year students tend to believe that vaccine is the most efficient preventive measure (medium value ± standard deviation; 1.2±0.1 vs. 0.7±0.1; p
Keywords: COVID-19, medical students, pharmacotherapy, questionnaire